Downconversion luminescence-based nanosensor for label-free detection of explosives - Malik, Monika; Padhye, Preeti; Poddar, Pankaj (Acs Omega, 2019)
We report a selective and sensitive nanosensor probe based on polyethylenimine (PEI)-capped downconverting nanophosphors beta-NaYF4:Gd3+, Tb3+@PEI for the detection of 2,4,6-trinitrotoluene (TNT), both in water and buffer media. These downconverting phosphors were synthesized via a hydrothermal route and are known to show excellent chemical, thermal, and photostability. They emit sharp emission peaks centered at similar to 488, 544, 584, and 619 nm, among which the peak at similar to 544 nm was remarkably quenched (similar to 90%) by the addition of TNT without giving any new emission peak. The sensing mechanism is based on the formation of a Meisenheimer complex between the electron-rich amine-functionalized beta-NaYF4:Gd3+, Tb3+ nanophosphors and electron-deficient TNT molecule, which was prominently visualized by the change in the color of the solution from whitish to brownish yellow, enabling visual detection, followed by luminescence resonance energy transfer between the nanophosphors and the complex. A linear range for TNT detection was obtained from 0.1 to 300 mu M with a limit of detection as low as 119.9 nM. This method displayed excellent selectivity toward TNT over other nitroaromatic compounds, which had no influence on the detection. Moreover, various other classes of analytes, viz., amino acids, pesticides, and sugars, did not quench the luminescence intensity of the nanophosphors. This developed nanosensor probe possesses high, stable fluorescence brightness and capability for the selective and sensitive on-site recognition of TNT molecules in aqueous media, avoiding complicated strategies and instruments. Thus, this work promises to pave ways to many applications in the detection of ultratrace analytes.